Navigating Changes in Patient Drug and Non-Drug Item Demands in Community Pharmacies Amidst the COVID-19 Pandemic: Changes in drug demand during COVID19 - Elayeh, Eman R.; Haddadin, Randa N.; Dawud, Razan J.; Alsinjlawi, Heba o.; Zidan, Rahaf k. (Jordan Journal of Pharmaceutical Sciences, 2024)
During the COVID-19 pandemic, healthcare systems worldwide faced unprecedented challenges, with pharmacists playing a crucial role on the frontlines. They encountered a surge in patient requests for drugs and non-drug items related to the treatment and prevention of the disease. This cross-sectional survey aimed to assess changes in demand for selected drugs and non-drug items from the perspective of pharmacists in Jordan in the period from March to June 2021, and to explore the factors influencing this demand. An online questionnaire targeting pharmacists working in community pharmacies was developed, validated, and disseminated using social media (e.g., WhatsApp, Facebook, and Messenger). The study collected 390 responses from pharmacists working in community pharmacies. The findings revealed significant increases in demand for prescription drugs such as antibiotics (97.4%), antithrombotics (84.1%), and antivirals (66.2%), often without prescriptions. Non-prescription items, specifically minerals and vitamins, were highly sought after (100%). Demand also rose for non-drug items such as thermometers (89.0%), oximeters (85.1%) and oxygen concentrators (68.2%). Changes in drug requirements were consistent across Jordan’s districts. However, an association was observed between the increase in demand for antivirals and herbal supplements and chain pharmacies (p-value 0.037 and p-value <0.005, respectively). In conclusion, COVID-19 led to a significant upsurge in the demand for pharmaceutical products and devices, placing immense pressure on community pharmacies. The public's reaction to the pandemic, to combat and manage the disease, was consistent across Jordan, regardless of social, financial, and spatial differences among the population. The study highlights the importance of adequately preparing and educating pharmacists to provide accurate information and counseling to patients in such circumstances. Therefore, health authorities must ensure that pharmacists have access to the latest treatments and management protocols and provide clear guidance on using home treatment devices to the public.